In this paper I can't understand the following

A given system has the potential energy $ U(x_1,x_2,x_3)=k_1 x_1^2 + k_2 (x_2-x_1)^2 + k_3 x_3^2 $.
Since the energy is quadratic, the correlation matrix is given in terms of the Hamiltonian matrix $H$ by $ <x_i x_j> = k_BT (H^{−1})_{ij} \quad $ with $ \quad H_{ij}=\frac{\partial^2 U}{\partial x_i \partial x_j} \quad $

  • $\begingroup$ shouldn't you also use kinetic energy in the partition function? $\endgroup$
    – dan-ros
    Commented Jun 20, 2016 at 10:55
  • 1
    $\begingroup$ @tonydo That would only give you a multiplicative constant $\endgroup$
    – valerio
    Commented Jun 20, 2016 at 11:01
  • $\begingroup$ I should write the sum as an integral instead maybe, I'll try a bit later $\endgroup$
    – David
    Commented Jun 20, 2016 at 11:14
  • $\begingroup$ Ok so I used integrals instead as the variables are continuous (edit). I get something that looks like the expected result but I still miss something. $\endgroup$
    – David
    Commented Jun 20, 2016 at 15:38
  • $\begingroup$ I have something which can relate your edit with the $(H^{-1})_{ij}$ matrix. Why did you erase it? If it was wrong, post a correct version and that maybe help with my calculus (which may be wrong, of course ^^") $\endgroup$ Commented Jun 20, 2016 at 16:35

1 Answer 1


A system is in a heat bath of temperature T so we work with the canonical ensemble. We consider $N$ degrees of freedom $x_1, x_2, ..., x_N$ and $x$ is the vector $(x_1~ x_2 ~ ... ~ x_N)^T$. The potential energy is quadratic so it can be expressed as a function of its second derivatives:

$ U=\sum_{i,j} x_i ~H_{i,j} ~x_j = x^T H x ~~ $ with $H_{i,j}=\frac{\partial^2 U}{\partial x_i \partial x_j}$.

$H$ is assumed invertible. The partition function $Z$ in the canonical ensemble is:

$ Z= \int (d^Nx) ~ e^{ -\frac{1}{2} \beta x^T H x} ~ = ~ \sqrt{\frac{(2 \pi)^N}{\det(H)}}~~ $ with $~~\beta=\frac{1}{k_BT}$,

where we used the multivariate Gaussian formula.

$ <x_i x_j> = \frac{1}{Z} \int (d^Nx) ~ x_i x_j e^{ -\frac{1}{2} \beta x^T H x} $

$ = \frac{1}{Z} (-\frac{2}{\beta})\frac{\partial}{\partial H_{i,j}}\int (d^Nx) ~ e^{ -\frac{1}{2} \beta x^T H x} $

$ = -2k_BT \frac{1}{Z} \frac{\partial Z}{\partial H_{i,j}} $

$ = -2k_BT \frac{\partial \ln(Z)}{\partial H_{i,j}} $

We plug-in the expression of $Z$ that we found above:

$ <x_i x_j>= k_BT \frac{\partial }{\partial H_{i,j}}(\ln(\det(H)) $

$H$ is invertible so we use Jacobi's formula:

$ \frac{\partial }{\partial H_{i,j}}(\ln(\det(H)) = Tr(H^{-1} \frac{\partial H}{\partial H_{i,j}}) $

$\frac{\partial H}{\partial H_{i,j}}$ is a matrix for which the element $\{i,j\}$ is $1$ and all other elements are $0$. In other words:

$ E\equiv \frac{\partial H}{\partial H_{i,j}} $ with $ E_{k,l}=\delta_{k,i} \delta_{l,j}. $

$ Tr(H^{-1} \frac{\partial H}{\partial H_{i,j}}) = Tr(H^{-1}E) $

$ (H^{-1}E)_{k,l}=\sum_m H^{-1}_{k,m}E_{m,l}=\sum_m H^{-1}_{k,m}\delta_{m,i}\delta_{j,l} = H^{-1}_{k,i} \delta_{j,l} $

$ Tr(H^{-1} E)=\sum_n (H^{-1}E)_{n,n}=\sum_n H^{-1}_{n,i} \delta_{j,n} = H^{-1}_{j,i} = H^{-1}_{i,j} $


$ <x_i x_j> = k_B T H^{-1}_{i,j} $


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.